Технологія блокчейн як об'єкт промислової власності: характеристика патентної активності - Артамонова, Неоніла Олегівна; Лерантович, Еліна Томашівна (Науково-дослідний інститут інтелектуальної власності Національної академії правових наук України, 2018)
У статті розглянуто деякі аспекти конкурентоспроможності та сучасного стану технології блокчейн. Проаналізовано патентний ландшафт блокчейну, виявлено провідні країни та компанії, показано динаміку патентування, тематичну структуру патентів, цитування патентів. Зроблено висновки про високу патентоспроможність технології блокчейн її перспективність і необхідність подальшого висвітлення специфічних аспектів у правовому та технологічному полі блокчейну.

The article gives an assessment of the current state and technological profile of blockchain in the global innovation space. Comparison of the level of inventive activity in the global scale of the blockchain development sector made it possible to identify countries with higher efficiency of scientific and technical activities — the USA and China. An increased patent activity of world corporations was noted, which indicates the use of patenting as a tool for creating a temporary monopoly on the market and for creating new markets based on the principle of "primacy" of access to the consumer. The active patenting of blockchain in the international PCT system, more than 30 %, indicates its high importance and prospects. The race of corporations for leadership changes the patent landscape every month. Today, IBM, nChain Holdings Limited, takes the first place, and MasterCard International Incorporated has moved to the third place. The structure of the technological profile of blockchain in the global innovation space is defined, which includes: a hybrid blockchain; methods and systems of blockchain using digital signatures; software testing, computerized scoring based on text and visual feedback; integration of market exchange and processing of issuers of transactions; blockchain security; identity management service to ensure the certification of transactions, etc. Conclusions are made about the high patentability of blockchain, its prospects and the need to further highlight specific aspects in the legal and technological field of the blockchain. However, understanding the existing limitations and disadvantages of the approach, the analysis of patent information can be actively used to understand the key trends in technological development, providing the necessary information basis for the formation of effective evidence-based scientific, technical and innovation policies.
Technology blokchein as an industrial property object: patent activity characteristic
Keywords: динаміка патентування; винаходи; база даних Patentscope; ІТ-технології; цифрова революція; blockade; patent analysis; inventions; data base Patentscope; IT-technologies; innovations; objects of intellectual property; patent landscape